Separation of double-wall carbon nanotubes by electronic type and diameter. Issue 7 (2nd February 2017) - Streit, J. K.; Lam, S.; Piao, Y.; Hight Walker, A. R.; Fagan, J. A.; Zheng, M.
Abstract : A new separation procedure is introduced to sort double-wall carbon nanotubes by electronic structure and diameter. Abstract : We introduce a new procedure for the efficient isolation and subsequent separation of double-wall carbon nanotubes (DWCNTs). A simplified, rate zonal ultracentrifugation (RZU) process is first applied to obtain samples of highly-enriched DWCNTs from a raw carbon nanotube material that has both single- and double-wall carbon nanotubes. Using this purified DWCNT suspension, we demonstrate for the first time that DWCNTs can be further processed using aqueous two-phase extraction (ATPE) for sequential separation by electronic structure and diameter. Additionally, we introduce analytical ultracentrifugation (AUC) as a new method for DWCNT characterization to assess DWCNT purity in separated samples. Results from AUC analysis are utilized to compare two DWCNT separation schemes. We find that RZU processing followed by sequential bandgap and diameter sorting via ATPE provides samples of highest DWCNT enrichment, whereas single-step redox sorting of the same raw material through ATPE yields SWCNT/DWCNT mixtures of similar diameter and electronic character. The presented methods offer significant advancement in DWCNT processing and separation while also providing a promising alternative for DWCNT sample analysis.